Structure and Vibrational Spectra of N,N-Dimethyl-N' (2-chlorobenzoyl)thiourea: Hartree-Fock and Density Functional Theory Studies - ARSLAN, HAKAN; MEHMET EMEN, FATIH; KULCU, NEVZAT (Asian Journal of Chemistry, 2010)
The molecular geometry and vibrational frequencies of N,N-dimethyl-N'(2-chlorobenzoyl)thiourea in the ground state has been calculated using the Hartree-Fock and density functional using Becke's three-parameter hybrid method with the Lee, Yang and Parr correlation functional (B3LYP) methods with 6-31G(d) and 6-311G(d) basis sets. The computational frequencies are in good agreement with the results of observed and normal coordinate analysis. The comparison of the observed fundamental vibrational frequencies of N,N-dimethyl- N'(2-chlorobenzoyl)thiourea and calculated density functional B3LYP and Hartree-Fock methods indicate that B3LYP is superior to the scaled Hartree-Fock approach for molecular vibrational problems.